Longitudinal Variations of Body Characteristics in Italian Elite Adolescent Football Players: An Observational Study - Stefania Toselli; Davide Latini; Alessia Grigoletto; Mario Mauro (Applied Sciences, 2025)
(1) Background: Body characteristics and physical skills affect field performance, and longitudinal improvements of these features allow one to join elite teams. This pilot study aims to investigate longitudinal changes (30 months) in 24 adolescent football players of an elite Italian club. (2) Methods: Participants were clustered according to their age (U10 = 8, U11 = 11, U12 = 5). Anthropometry and body composition assessments were performed following standardized methods. Countermovement jump (CMJ), maximal speed (15 m), and change of direction (RSA) were tested. The repeated-measures ANOVA was assessed for the interaction effect between time and category. The Pearson correlation product–moment was used to correlate the changes (∆) in physical performance and body characteristics. Also, each delta of performance skill was used as the dependent variable in a multiple linear regression model. (3) Results: Stature, body mass, fat-free mass (FFM), total upper area (TUA), total calf area (TCA), and CMJ improved in all categories (p < 0.05). The lower limb power variability was better explained by humeral diameter and the supraspinal skinfold thickness variation (adj-R2 = 0.621 p < 0.001), while both maximal speed and RSA were negatively affected by the calf fat index (p < 0.01). (4) Conclusions: To face the complexity of human physiology and ameliorate the monitoring process in youth, football technicians need deeper insight into how body shapes and performance can vary over growth.